Flagellin-Fused Protein Targeting M2e and HA2 Induces Innate and T-Cell Responses in Mice of Different Genetic Lines - Liudmila A. Stepanova; Marina A. Shuklina; Kirill A. Vasiliev; Anna A. Kovaleva; Inna G. Vidyaeva; Yana A. Zabrodskaya; Alexandr V. Korotkov; Liudmila M. Tsybalova (Vaccines, 2022)
Efficient control of influenza A infection can potentially be achieved through the development of broad-spectrum vaccines. Recombinant proteins incorporating conserved influenza A virus peptides are one of the platforms for the development of cross-protective influenza vaccines. We constructed a recombinant protein Flg-HA2-2-4M2ehs, in which the extracellular domain of the M2 protein (M2e) and the sequence (aa76-130) of the second subunit of HA (HA2) were used as target antigens. In this study, we investigated the ability of the Flg-HA2-2-4M2ehs protein to activate innate immunity and stimulate the formation of T-cell response in mice of different genetic lines after intranasal immunization. Our studies showed that the Flg-HA2-2-4M2ehs protein was manifested in an increase in the relative content of neutrophils, monocytes, and interstitial macrophages, against the backdrop of a decrease in the level of dendritic cells and increased expression in the CD86 marker. In the lungs of BALB/c mice, immunization with the Flg-HA2-2-4M2ehs protein induced the formation of antigen-specific CD4+ and CD8+ effector memory T cells, producing TNF-α. In mice C57Bl/6, the formation of antigen-specific effector CD8+ T cells, predominantly producing IFN-γ+, was demonstrated. The data obtained showed the formation of CD8+ and CD4+ effector memory T cells expressing the CD107a.